Clay Mineral Characterisation of the Major Soil Series of Trivandrum District - Asharaf M (Department of soil science and agricultural chemistry, College of Agriculture, 1992)
The Trivandrum, Nedumangad Palode soil series are the major soil series established in The Trivandrum District. A study was undertaken to gather detailed qualitative and quantitative clay mineralogy of these soil series taking one representative the soil profile from each of the series. From the information on the field morphology, temperature and moisture regimes and mineralogy, it has been attempted to classify these soil series as per soil Taxonomy (USDA, 1975, 1987) upto the family level. The Trivandrum soil series situated in the mid land laterite zone of the Trivandrum District 20-25 meters above M.S.L. and 15-20 km away from the sea. While the Nedumangad and palode series is situated in the mid upland laterite zone, 25-50 meters above M.S.L. and 30-60 km away from the sea. The Trivandrum and Nedumangad series are comes under denudaded and cultivated laterite tract while the palode series comes under the retained semievergreen lateritic tract. All the three series are developed from the geneissic rocks rich in ilemanite and biotitemica. The laterisation is in the increasing order from palode < Nedumangad < Trivandrum series with developing lateritic argillic horizon (B12) and laterized Kaolinitic (B2t) horizons respectively. The Trivandrum and Nedumangad series are red to reddish brown coloured while the Palode series dark greyish brown to black coloured with gravelly sandy clay to gravelly clay texture. In all the three soil series the gravels are clay from the principal major components more than 45 per cent and more than 30 per cent respectively. The clay increase down the profiles is about two times in Trivandrum and Nedumangad series and it is about 1.5 times increase in Palode series. The Trivandrum and Nedumangad series are with Ochric epipedons and Kandic diagnostic subsurface horizon, while the Palode series is with mollic epipedon and developing lateritic argillic subsurface diagnostic horizons. All the soils are acidic, non saline and with low CEC. In the Trivandrum and Nedumangad series, the CEC is < 10 cmol kg -1 and in Palode series it is > 10 cmol kg-1. Hence the Trivandrum and Nedumangad series become Kaolinitic and low activity clay (LAC) soils and the Palode series is mixed and comparatively active clay soils. The sand mineralogy contains quartz, and leucoxene, heamatite, biotite, sillimanite in all the three soils series indicating the uniformity of parent materials. The chemical analysis and X-ray diffraction analysis reveal appreciable amounts of kaolinite (60-80 per cent), in the Trivandrum and Nedumangad series and 30-40 per cent in the Palode series. The AFAS also forms significant amount in the increasing order Trivandrum <Nedumangad <Palode comparatively appreciable amount of vermiculite, smectite and mica are present in the Palode series (10-20 per cent) imparting a mixed mineralogy to clay. From the available information from the field observation and gathered information on moisture, temperature regimes, the Trivandrum, Nedumangad and Palode series are temtatively classified initially as Kandiustelts, Kan haplic Haplustalfs and Typic Hapuldolls respectively. Finally with the gathered information in the mixture, mineralogy, these soils were finally classified upto family level as follows. Trivandrum series : Fine skeletal kaolinitic isohyperthermic family of kandiustults. Nedumangad series : Fine skeletal kaoliniticisohyperthermic family of kanhaplic Haplustalfs. Palode series : Coarse skeletal mixed isohyperthermic family of typic Hapludolls.